Modeling the behavior of air bubbles in the field of stationary arc discharge - Петров, Станіслав Володимирович; Бондаренко, Сергій Григорович; Рубець, Денис Ігорович; Саванчук, Олександр Валерійович; Янюк, Вероніка Андріївна (Eastern-European Journal of Enterprise Technologies, 2013)
The article discusses the processes occurring at the electric arc discharge in the pore (bubble) liquid. The results of modeling of the dynamics of the behavior of a single bubble in the field of the stationary arc discharge were presented. To describe such a discharge a homogeneous model of a short cylinder was used. The model was supplemented by the equations that permit to determine the plasma density and its pressure in the discharge channel. The change of the size of the gas bubble was determined during its breakdown, taking into account the evaporation and condensation of steam and for the account of the radial motion of the bubble. The equations of the critical pressure inside the gas bubble were obtained, and on the basis of the first law of thermodynamics the temperature inside it was determined. The equations of the intensity of heat and mass transfer through the surface of the gas bubble were obtained on the basis of the molecular kinetic theory. To solve the equations of the mathematical model an algorithm, implemented in the environment Mathcad was developed. The kinetic, dynamic and energetic characteristics of the behavior of the gas bubble in the field of the arc discharge were obtained